Steroid and Triterpenoid Compounds with Antiparasitic Properties - Kuzminac, Ivana Z.; Savić, Marina P.; Ajduković, Jovana. J.; Nikolić, Andrea R. (Current Topics in Medicinal Chemistry, 2023)
Parasitic diseases affect millions of people and animals, predominantly in the tropics, including visitors to tropical countries and other areas. Efficient and low-cost treatments for infections caused by various parasites are not yet available. Antiparasitic drugs have some drawbacks, such as toxicity and the development of resistance by parasites. This has motivated many researchers to focus on the discovery of safe, effective and affordable antiparasitic drugs, both among drugs already available for other diseases and new compounds synthesized or isolated from natural sources. Furthermore, steroid and triterpenoid compounds attract the attention of pharmacologists, chemists and biochemists owing to their broad application in the treatment of various diseases. Isolation of steroid and triterpenoid compounds from natural sources with antiparasitic efficacy is an attractive choice for scientists. On the other hand, these compounds can be transformed into more potent forms by modifying the basic skeleton. This review presents a collection of isolated and synthesized steroid and triterpenoid compounds from 2018 to 2021 that have been reported to be effective against certain parasitic protozoa and helminths. A total of 258 compounds have been identified with antimalarial, antitrypanosomal, antileishmanial, anti-Toxoplasma, and/or anthelmintic activity. The described investigations of antiparasitic compounds may be helpful for further drug development.
Keywords: Malaria